2016
DOI: 10.15405/epsbs.2016.11.82
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation and Life Satisfaction in University Students: Gender Differences

Abstract: This study aimed to compare gender differences in nine strategies of cognitive emotion regulation and to predict life satisfaction through these strategies. The participants consisted of 302 students (202 female and 100 male) of Allameh Tabataba'i University that were selected through Multi-stage cluster sampling and assessed by Satisfaction with Life Scale (SWLS), and Cognitive Emotion Regulation Questionnaire (CERQ). The results showed that females reported more usage of Rumination while strategies of Positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
(35 reference statements)
1
1
0
6
Order By: Relevance
“…It was understood from the studies that women fell short compared to men in using active coping strategies, which concurs with the work ofVingerhoets & Van Heck [51]. Similar results were also found in a recent study in Iran using CERQ and SWLS [52], but women were slightly more satisfied there. Knowing these differences women themselves can be aware of their emotional regulation in certain situations.…”
Section: Discussionsupporting
confidence: 88%
“…It was understood from the studies that women fell short compared to men in using active coping strategies, which concurs with the work ofVingerhoets & Van Heck [51]. Similar results were also found in a recent study in Iran using CERQ and SWLS [52], but women were slightly more satisfied there. Knowing these differences women themselves can be aware of their emotional regulation in certain situations.…”
Section: Discussionsupporting
confidence: 88%
“…En cuanto a las diferencias de sexo halladas en el uso de las estrategias de afrontamiento cognitivo, los resultados encontrados corroboran los hallazgos de estudios previos (e.g., Chamizo-Nieto et al, 2020; Esmaeilinasab et al, 2016;Mumtaz et al, 2017;Potard et al, 2021), donde se observa que los chicos parecen que tienden a utilizar con más frecuencia estrategias de afrontamiento más adaptativas, además de la estrategia de culpar a los demás, para afrontar las situaciones difíciles en comparación con las chicas. En cambio, ellas tienden a rumiar más sobre las experiencias como forma de gestionar esas emociones generadas, confirmándose la hipótesis 4.…”
Section: Discussionunclassified
“…Además, la literatura científica ha explorado y analizado las posibles diferencias en función del sexo en las conductas de acoso y ciberacoso, así como en la frecuencia de uso de las estrategias de afrontamiento cognitivo (e.g., Chamizo En cuanto a las estrategias de afrontamiento, en investigaciones previas también se encuentran resultados diferenciales en relación con las diferencias de sexo. Algunos hallazgos previos señalan que los chicos tienden a usar más frecuentemente la aceptación (Mumtaz et al, 2017), la focalización positiva, la planificación (Esmaeilinasab et al, 2016), la reevaluación positiva y el culpar a otros (Potard et al, 2021) en comparación a las chicas para manejar las situaciones estresantes. Mientras que ellas suelen emplear con más frecuencia la rumiación (Balzarotti et Por ello, para intentar profundizar en el conocimiento existente en la literatura científica en torno al acoso, el ciberacoso y las estrategias de afrontamiento cognitivo, así como para esclarecer los hallazgos diversos sobre las diferencias de sexo en estas variables, se plantearon dos objetivos en este estudio.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Fabes et al (10) considered these scales as theoretically distinct and suggested the need for additional research. Though the content of these strategies differs (i.e., emotion focused reactions focus on the child's negative emotions while problem focused reactions address an external cause of those emotions), parents rarely use just one method to cope with stress, and their attempts are often combinations of different methods (34)(35)(36)(37). These factors may differentially predict child outcomes (8,10) and are indeed theoretically distinct, but the present findings combined with the results of Fabes et al (10) suggest that they are considered a single factor.…”
Section: Discussionmentioning
confidence: 99%